Can Landuse Intensification Decrease Soil Carbon Stock in Upstream Sumber Brantas Watershed? - Anita Dwy Fitria; Syahrul Kurniawan (Jurnal Biologi Tropis, 2023)
Upper Brantas watershed with volcanic ash soil has potentially high carbon stock. However, land-use intensification in the upstream watershed area is the potential deterioration of soil quality, mainly degradation. The study aimed to assess the effect of land-use intensification in the upper Sumberbrantas watershed on soil carbon stock. The study was conducted in the upper Sumber brantas watershed, particularly in Kali kungkuk micro watershed, Batu City, East Java – Indonesia. Soil samples were taken at 0-30 cm and 30-100 cm on 4 land uses (i.e., forest, agroforestry, cropland, and shrubland) with three replications. The variable measured include basal area, standing litter mass, soil bulk density, and soil organic C. The results showed that land-use intensification strongly impacted soil carbon stock at 0-30 cm and 30-100 cm depth of soil. The soil carbon stock degradation of around 60% to 67% in the intensive cropping systems and in the post-cropping cultivation was covered by a shrub as compared to the forest soil, especially at a depth of 0–30 cm. The correlation value (p<0.05) between the basal area (0.65) and standing litter mass (0.42) on soil carbon stock, especially at a depth of 0-30 cm, indicated that the basal area and standing litter mass increase soil carbon stock. The result was in line with the soil bulk density by ANOVA test at a depth of 0-30 cm and 30-100 cm showing the effect (p<0.05) where intensive land use consisting of treeless (i.e., cropland and shrubland) increases the soil bulk density.